ANALISIS RISIKO PENGELOLAAN DAN KEUANGAN DALAM MENINGKATKAN PENDAPATAN USAHATANI TOMAT (LYCOPERSICUM ESCULENTUMMILL) DI KECAMATAN BERASTAGI KABUPATEN KARO PROVINSI SUMATERA UTARA - Marleni Marleni; Tri Martial; Syahbudin Hasibuan (AGRIBIOS, 2025)
Agriculture plays an important role in the economic development of rural communities because most community members in Indonesia depend on the agricultural sector. The agricultural sector until now, still gets the main priority in driving development. With the development of horticulture in vegetable commodities, there is an increase in public concern for health. Tomato production often fluctuates and the main factor that causes a decrease and fluctuation in tomato production is due to high production risk factors, besides that farmers also have financial problems that have an impact on farm income. The purpose of this study was to determine the production and financial risks to tomato farm income in Berastagi District, Karo Regency. The research method combines qualitative and quantitative approaches reinforced by taking questionnaires to farmers using structural equation modelling data analysis with 57 farmers. The results showed that production risk had a moderate effect on tomato farm income and finance had a large effect on tomato farm income.